Pengembangan RPP-LKPD Berbasis Model Pembelajaran Ber2P3 Terhadap Penguasaan Konsep Siswa Pada Materi Getaran dan Gelombang - Gita Fadilla Kasim; Mursalin Mursalin; Frida Maryati Yusuf; Masri Kudrat Umar; Tirtawaty Abdjul; Supartin Supartin (Jurnal Penelitian Pendidikan IPA, 2024)
This research is development research that aims to describe the validity, practicality and effectiveness of learning devices using the Ber2P3 learning model in the form of lesson plans and LKPD on Vibration and Wave material with research subjects involving 25 students of class VIII Tahfiz MTs Al Huda Gorontalo. Based on the validity of the RPP and LKPD based on the Ber2P3 learning model, it meets the valid criteria with an average value of 90%, the practicality of the RPP based on the Ber2P3 Learning model as seen from the implementation of learning with the first and second meeting values ranging from 78% and 87% including good criteria. Student responses meet the good criteria with a score of 80%. The effectiveness of RPP and LKPD Ber2P3 is seen through the activities of students who meet the good criteria with a value of 83% and a learning outcome test with 84% classical completeness. Based on the results of the study, it can be concluded that the lesson plans and LKPD using the Ber2P3 learning model of vibration and wave material meet the criteria of valid practical and effective